THE EFFECTIVITY OF RELIGIOUS VALUES FOR THE EMPOWERMENT OF WOMEN TOWARDS THE WORKING BEHAVIOR IN SYARIAH ECONOMY PERSPECTIVE (EMPIRICAL STUDY OF NIGHTCLUB IN MAKASSAR) - Aisya, Sitti; Hamzah, Natsir; Abdullah, Wahyuddin; AR, Moh Sabri (Program Pascasarjana, UIN Alauddin Makassar, 2020)
Women are one of the most important resources for the sustainability of national development, they are a potential asset as the subject of development. These socio-economic problems trigger one of the reasons for women to work both as women with a single status and as married (mother and wife). The choice of THM as the last choice for women can provide maslahah for their family life. Makassar City is one of the cities with a significant THM development. Along with the development of the city of Makassar as a Metropolitan city towards the vision of a World city. However, working in a nightclub is a choice or a job option when faced with a situation. Women who work in nightclubs do not lose sight of the beliefs they have, the desire for a sufficient income and the lifestyle that triggers the work.